Chemistry Teachers’ Awareness, Understanding, and Confidence toward Computational Tools for Molecular Visualization - Saudale, F. Z.; Lerrick, R. I.; Parikesit, A. A.; Mariti, F. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Recent advances in cheminformatics and bioinformatics research have generated software and computational tools for molecular modeling and visualization that can be incorporated to improve chemistry teaching and learning in high school. Nevertheless, there have never been any study simultaneously reporting chemistry teachersÃ¢â‚¬â„¢ awareness, understanding, and confidence toward contemporary computer-aided molecular modeling and visualization tools. This study examined 32 high school chemistry teachersÃ¢â‚¬â„¢ knowledge, understanding and confidence toward nine new computational programs on molecular modeling and visualization namely ChemDraw, HyperChem, UCSF Chimera, Marvin Sketch, PsiPred, MBC (PS2), Rampage, Vienna RNA Package and Mode RNA following two days of professional workshop-based training.Ã‚Â After completing the training and assessments, the teachers showed an enhancement in awareness, understanding, and confidence toward those nine computational programs. Intensive activities consisting of theoretical lectures, hands-on practices, assignments, and case study presentations seem to provide valuable resources to the increase in teachersÃ¢â‚¬â„¢ knowledge, understanding, and skill that incorporates computational technology. Hence, the impact of this research pointed toward the value of teachersÃ¢â‚¬â„¢ professional development that creates a platform to reduce the barriers of access, resources, knowledge, and skills. This study is expected to help improving teachersÃ¢â‚¬â„¢ awareness, understanding, and confidence necessarily required for further implementation of available technology for instructional purposes.Ã‚Â